Relationship Banking, Governance and SME’s Performance: The Portuguese Evidence - Pinto, António (2014)
The aim of this work is to analyze how bank relationships, corporate governance and the interdependence that is established between them, affect corporate performance, based on a sample of 5,900 Portuguese SMEs. The banks and the enterprises establish relationships which enable them to overcome problems of asymmetrical information thereby overcoming difficulties felt in obtaining financial resources. In addition, the specificities that SMEs face, namely their ownership structure, as they are often owned and controlled by families, lead us to study the role played by corporate governance and the various control mechanisms in achieving corporate objectives. These features confer an important supervisory role on credit institutions.